Relation of the frequency and mortality of pulmonary thromboembolism with meteorological parameters - Perincek, Gökhan; Hatipoğlu, Osman Nuri; Tabakoğlu, Erhan; Avcı, Sema (Acta Biomedica Atenei Parmensis, 2018)
Objective: The objective of this study is to find the relationship between incidence rate and mortality of acute pulmonary thromboembolism (PTE), and seasonal and meteorological factors. Materials and methods: The data from 234 patients who were hospitalized due to acute PTE in the emergency service or policlinics between 2001 and 2008 were investigated retrospectively. Cases that developed APE (acute pulmonary embolism) in the hospital were excluded. Seasons and months in which acute PTE was diagnosed were recorded. Mortality rates by months and seasons were evaluated. The mean pressure, temperature and humidity values were evaluated for periods of three days, seven days and one month before the day of presentation. The effects of meteorological factors on the severity (massive or non-massive) and mortality of APE were investigated. Results: The incidence rate of acute APE showed a significant difference according to seasons (p=0.000). APE was diagnosed most commonly in spring and winter. The mean pressure values for three days, seven days and one month and the mean humidity values for three days for the dead patients were found to be significantly lower than those of the survived ones (p